Do Environmental Taxes Improve Environmental Quality? : Evidence from OECD Countries - Sokolova, Yuliia (2021)
This master’s thesis investigates the relationship between environmentally related taxes in OECD countries and air quality, represented by carbon dioxide and greenhouse gas emission levels. The thesis provides statistical analysis of data on environmental taxes and their types, as well as other variables that might affect air quality in the OECD member countries. Panel data analysis has shown statistical significance in one out of four equations, so the comparative analysis on the sample of OECD countries that are also European Union members was performed. The analysis has shown a statistically significant positive effect of environmentally related tax revenues on the air emission levels, however, once the same models were applied on the OECD countries sample, the significance did not hold.